Experiment Ball Levitation with Fuzzy PID and PID Implementation - Nguyen, Hoang-Thuat; Dao, Anh-Quan; Hoang, Van-Phu-Quy; Nguyen, Quyen-Anh; Dang, Truong-Phu; Tang, Minh-Nam; Le, Vu-Huy; Bui, The-Nam-Vuong; Nguyen, Tien-Dung; Le, Thi-Hong-Lam (Peneliti Teknologi Teknik Indonesia, 2024)
The “Ball Levitation” experiment can be easily recognized, like iFly in Singapore, and is greatly integrated into industrial fields such as flow control systems, aerodynamic testing, the oil and gas industry, HVAC systems, etc. Therefore, it is utilized in university laboratories for student exploration of non-linear control technology. The main objective of this experiment is through the position of the ball which is measured by an ultrasonic sensor to execute the PWM of the blower fan in order to control the speed of one so that the ball can be stabilized consistently at a specific height. Despite its uncomplicated model, the challenge of this model is from non-linear effects on the ball and the intricate physics governing its movement. Moreover, the ball is highly responsive to external influences from the blower fan. Consequently, conventional mathematical control methods struggle to handle it, making the simulation and comparison of control algorithms challenging. A Fuzzy-PID controller is meticulously designed to automatically stabilize the ball's position by considering the PID parameters with pre-defined fuzzy rules due to the actual showcase of the model. This setup allows us to experimentally compare the traditional PID controller with the Fuzzy-PID controller. The results reveal notable differences in the performance characteristics of these controllers.